THE DEVELOPMENT OF E-CRM FOR THE SERVICE IMPROVEMENT AT THE UNIVERSITIES - Sriyanto Sriyanto; Sri Karnila; Nurjoko Nurjoko (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Public Universitiesand Private Universities are recently contesting each other to improve their qualities and facilities in order to attract new students to come in. The high quality and the number of facilities belonging to universities are not a guarantee to get prospective students as they are targeting. This phenomenon occurs due to many factors. One of the factors causing the matter is that the way in delivering information to the prospective students and their parents is not right and not compatible with their needs so that the prospective students and their parents do not know the quality, the educational programs, the facilities, and another information which belong to the universities. It also occurs in IBI Darmajaya, one of the top private universities in Lampung. According to the obtaineddata of this research, the number of the new students who joinedgenerally decline compared with the previous year; while, the number of students who did not finish theirstudy was high enough. One of the solutions to overcome these problems was by providing information through the exact media which provided the needs of the prospective students and their parents. By using this way, it was expected to convince the prospective students to join and to finish their study.In order to provide the information which was compatible with the needs of the prospective students and their parents, the E-CRM system equipped by the data mining was developed. The database which was provided in IBI Darmajaya was processed by the data mining in order to be used as an input for the E-CRM system. This system providedthe information for the relevant unit about what the informational media which had to be used were and what information which should be given to the prospective students and their parents was. To find out the successfulness of the implementation of this system, the Critical Success Factor (CSF) was carried out. The result of the CSF was used for the improvement of the system and the expansion of the system of the E-CRM.Key Words:E-CRM, Zachman, CSFTHE DEVELOPMENT OF E-CRM FOR THE SERVICE IMPROVEMENT AT THE UNIVERSITIES